Evaluación de la actividad anticancerígena de una proteína hipotética recombinante (PHP- 1) de Polaromonas sp. (2021)
Cervical cancer has a high mortality rate among women, being one of the malignant neoplasms with the highest incidence. Current therapeutic options are highly invasive; For this reason, treatment alternatives with fewer side effects and invasiveness are necessary. Potential new therapeutic options include anticancer peptides and proteins derived from antimicrobial peptides. The purpose of this study was to evaluate the cytotoxic effect and the cell death mechanism of the hypothetical protein PHP-1 of the psychrophilic microorganism Polaromonas sp. in the cervical cancer cell line. Through bioinformatic analysis, it was shown that PHP-1 exhibits structural characteristics typical of anti-cancer peptides and proteins. The cytotoxicity of PHP-1 was evaluated by an MTT test that showed a dose and time-dependent effect. The effects generated were additionally analyzed by means of an annexin V / PI labeling, indicating that the hypothetical protein induces apoptosis, which correlates with the observed morphological changes. The results of this work represent the first functional study of the hypothetical protein PHP-1 and suggest that PHP-1 is cytotoxic for the HeLa cell line by inducing cell apoptosis, highlighting its potential as an anticancer agent.